Biology of Anastatus dasyni Ferr (Hymenoptera: Eupelmidae) on Egg of Dasynus piperis China (Hemiptera: Coreidae) - IM TRISAWA; AUNU RAUF; UTOMO KARTOSUWONDO (HAYATI Journal of Biosciences, 2007)
Anastatus dasyni Ferr wasp (Hymenoptera: Eupelmidae) is one of the parasitoids attacking eggs of the pepper berry sucking bug, Dasynus piperis China (Hemiptera: Coreidae). Study was conducted in the laboratory to determine immature development, adult longevity, fecundity, sex ratio, oviposition preference, and number of host parasitized. The result showed that immature development time from egg up to adult was 15.57 + 0.09 days, mean fecundity was 99.45 + 5.60 eggs, and sex ratio (% of females) was 67.28 + 0.56%. If provided with honey 10% and host eggs, females lived for 37.7 + 2.78 days and males 6.30 + 0.56 days. Host eggs aged one and two days were more preferred by A. dasyni for oviposition. Mean number of hosts parasitized by this wasp aged less than one day was much lower as compared to the older one. Key words: pepper, pepper berry sucking bug, Dasynus piperis, parasitoid, Anastatus dasyni